PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI PENGEMBANGAN BAHAN AJAR BERBASIS WEBSITE - Alif Ringga Persada (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2017)
At globalization era in this time process the study challenge which big relative, related to technological science growth ( Very extraordinary IPTEK). very the fast Growth IPTEK offer to us various amenity in obtaining and mengolah information. Especially vary it study media which can be used by a teacher at the (time) of submitting study items. development of teaching Substance which is is made by by a researcher is substance development teach to base on the Website of at address of web belajarmatematika.id. Intention of this research is : 1)Mengetahui use of study media base on the e-learning ( Website) at school 2) Yielding product of study media